Intrapreneurship education in the dual education system. (2016) - Frank, Hermann; Korunka, Christian; Lueger, Manfred; Weismeier-Sammer, Daniela
Intrapreneurship as a form of entrepreneurial behaviour has the potential to create substantial value for an enterprise. Intrapreneurs, as opposed to entrepreneurs, are usually active on a lower hierarchical level and confronted with the internal, rather than the external environment of an enterprise when engaging in entrepreneurial activities. Usually, intrapreneurs lack formal decision-making power and thus require special social competences to overcome challenges such as organisation-internal resistance. How can an enterprise train its employees to develop intrapreneurial behaviour? This paper analyses the apprenticeship training of three enterprises that are considered as good practice examples regarding innovativeness. The research results show that strict selection processes of apprentices, systematic vocational education and career planning, social integration, incentive systems, quality orientation and corporate social responsibility are conducive for the development of intrapreneurial behaviour.